GYRB – POLYMERASE CHAIN REACTION AND HISTOPATHOLOGIC CHARACTERISTIC FIGURE POTENTIAL FOR DETERMINING DIAGNOSIS OF TUBERCULOUS LYMPHADENITIS - Herlambang, Wahyu; Mertaniasih, Ni Made; Soedarsono, Soedarsono; Sandhika, Willy (African Journal of Infectious Diseases (AJID), 2023)
Background: TB lymphadenitis is still a problem that needs serious treatment. In Indonesia, it was reported that 53% of TB cases were extrapulmonary tuberculosis, with the most cases being Lymphadenitis TB, 11.6%. In children, 43% of extrapulmonary tuberculosis cases are TB lymphadenitis. Diagnosis is quite difficult; a method of determining the diagnosis and appropriate comprehensive treatment is required in managing TB Lymphadenitis. Materials and Methods: In this study, 15 fine needle aspiration biopsy aspirate samples were subjected to molecular examination using the gyrB–polymerase chain reaction method and histopathological observations using the smear method with hematoxylin-eosin staining. Observation of preparations using a microscope with a magnification of 200x. Results: The histopathological characteristics of the fine needle aspiration biopsy aspirate showed positive results in 4 out of 15 samples, with epithelioid cells arranged in a characteristic granuloma structure, necrotic debris was visible, and cells joined together to form multinucleated giant cells as an inflammatory response to complex infection. In this study, 6 out of 15 (40%) were detected to be positive in the diagnosis based on molecular detection using a specific target gene gyrB - polymerase chain reaction. Conclusion: Characteristic features on histopathological examination associated with gyrB - positive polymerase chain reaction on lymphadenitis fine needle aspiration biopsy aspirate samples can be used as a determinant diagnosis of tuberculous lymphadenitis.